Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Makmur Jaya Energi di Kota Tangerang - Fathan Arif; Roni Hutauruk; Denok Sunarsi (Peneliti.net, 2023)
This study aims to determine the effect of leadership style and work discipline on employee performance at PT Makmur Jaya Energi in Tangerang City, either partially or simultaneously. This type of research uses associative quantitative methods. The sampling technique uses a saturated sample of 64 respondents. The data analysis technique uses the data instrument test, the classical assumption test. Quantitative data analysis technique uses multiple linear regression, the coefficient of determination. Test the hypothesis using the t test and F test. The results of the analysis show: Leadership style partially affects employee performance with a simple linear regression equation Y = 15.329 + 0.607 X1. The correlation coefficient value is 0.701, meaning that it has a strong relationship and a determination coefficient of 0.492, meaning that performance is influenced by leadership style by 49.2%. This is evidenced by the t test obtained t count > t table (7.354 > 1.671) and reinforced by a significant value <0.05 (0.000 <0.05). Work discipline partially has a positive effect on employee performance, shown by the simple linear regression equation Y = 49.023 + 0.198 X2. The correlation coefficient value is 0.219 meaning that it has a strong relationship and a determination coefficient of 0.480 means that performance is influenced by work discipline by 48%. This is evidenced by the t test obtained t count > t table (1.968 > 1.671) and reinforced by a significance value <0.05 (0.000 <0.05). The results of the research on leadership style and work discipline simultaneously on employee performance are shown by the multiple linear regression equation Y = 19.940 + 0.649 X1 + 0.147 X2, the correlation coefficient value is 0.728 meaning that it has a strong relationship level and the coefficient of determination is 0.530 meaning that performance is influenced by style leadership and work discipline by 53% while the remaining 47% is influenced by other factors not examined. This is evidenced by the results of the F test hypothesis test obtained by F count > F table (27.061 > 3.15) and reinforced by a significance value <0.05 (0.000 <0.05). Thus it is proven that Ho is rejected and Ha is accepted.